Strategi Test-Driven Development dalam Arsitektur Microservices untuk Optimalisasi Pengembangan Aplikasi Payroll - Ai Dina Agustin; Abdul Hadi; Suratno Suratno (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2026)
The development of payroll systems based on microservices demands highly reliable software, particularly in inter-service communication. This study aims to evaluate the effectiveness of the Test-Driven Development (TDD) approach in improving software quality within a microservice-based Payroll system. A mixed method was employed, combining qualitative analysis of TDD implementation and quantitative measurements of code coverage and defect rate. The system was implemented across three main services: Auth Service, Employee Service, and Payroll Service, all accessed through an API Gateway. Results show that the TDD approach increased statement coverage up to 96.81% and reduced the defect rate to 4.33 per 1000 lines of code. These findings confirm that TDD significantly contributes to the reliability and robustness of testing in microservice architectures. The outcomes of this study provide a solid foundation for the broader application of TDD in other modular system developments.